Community-Based Grazing Marketing: Barriers and Benefits Related to the Adoption of Best Management Practices in Grazing Systems - Audrey E. H. King; Lauri M. Baker; Peter J. Tomlinson (Journal of Applied Communications, 2017)
Environmental impacts of less than optimal grazing management choices can be intense and widespread. Improved communication of responsible grazing practices known as best management practices (BMPs) may increase adoption of these practices and increase sustainability of grazing systems. Community-based social marketing (CBSM) is a tool that can be used by communicators to generate behavior changes. This strategy emphasizes the identification of barriers to goal behaviors and the development of strategies to overcome them. This study sought to identify barriers and benefits associated with the adoption of grazing BMPs. Barriers identified include water availability and quality, and leasing and renting land. Benefits identified were increased resiliency through rotational grazing, improved watering and burning practices.
Keywords: Opinion Leadership; Social Influence; Social Media; Water Quality